Synthesis And Characterization Of 1,3- Disubstituted Benzimidazolium Salts And Silver(I)-7v-Heterocyclic Carbene Complexes As Potential Ionic Liquid Crystals And Antibacterial Agents - Yeap, Choon Wan (2019)
This work involved the synthesis and characterization of 1,3-disubstituted benzimidazolium salts and their silver(I)-NHC complexes via A-alkylation method and silver base route. The results from Fourier-transform Infrared spectroscopy (FTIR), ‘H-NMR, 13C-NMR spectroscopy and CHN elemental analysis have revealed that the 1,3-disubstituted benzimidazolium salts and their silver(I)-NHC complexes were successfully prepared.